2014
DOI: 10.1002/bin.1393
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Antecedents and Consequences on the Occurrence of Bizarre Speech in Individuals With Dementia

Abstract: We conducted a series of assessments to determine the differential effects of common antecedents and consequences that can influence the occurrence of bizarre speech in three women with moderate to severe dementia. First, a traditional functional analysis was conducted to assess the function of bizarre speech. After results revealed differentially higher levels of bizarre speech during control sessions, an antecedent analysis was conducted. During this second assessment, all consequences were held constant, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 45 publications
(41 reference statements)
0
11
0
7
Order By: Relevance
“…It is possible that engaging with materials (often reading materials) may have competed with vocalizations. Trahan et al () demonstrated that antecedent events were more likely to differentially influence the occurrence of disruptive vocalizations in this population relative to consequences. Future researchers could examine the extent to which treatment planning based on the results of the descriptive assessment (i.e., removing antecedent events that are likely to evoke the target behavior) improves treatment outcomes when functional analyses are not feasible.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…It is possible that engaging with materials (often reading materials) may have competed with vocalizations. Trahan et al () demonstrated that antecedent events were more likely to differentially influence the occurrence of disruptive vocalizations in this population relative to consequences. Future researchers could examine the extent to which treatment planning based on the results of the descriptive assessment (i.e., removing antecedent events that are likely to evoke the target behavior) improves treatment outcomes when functional analyses are not feasible.…”
Section: Discussionmentioning
confidence: 92%
“…For example, Kodak, Northup, and Kelley () demonstrated that different forms of attention (e.g., reprimands and unrelated comments) produced differential responding for two children with developmental disabilities whose functional analysis results suggested that attention was a reinforcer for their problem behavior. Although the results of Trahan et al () showed undifferentiated responding across consequent manipulations, those results may have been confounded with antecedent manipulations that resulted in high rates of inappropriate speech (i.e., open‐ended questions). Future researchers could further evaluate the influence of consequent events in this context by evaluating consequences identified by way of a DA in the absence of strong antecedent control.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Of the nine studies on verbal behavior in dementia patients, four investigated verbal operants (Gross, Fuqua, & Merritt, ; Henry & Horne, ; Oleson & Baker, ; Trahan, Donaldson, McNabney, & Kahng, ). Other studies related to verbal behavior focused on disruptive vocalizations (Beaton, Peeler, & Harvey, ; Buchanan & Fisher, ; Locke & Mudford, and Trahan, Donaldson, McNabney, & Kahng, ).…”
Section: Resultsmentioning
confidence: 99%